Anesthesia Management in Pregnancy with Heart Disorder using Walking Epidural Analgesia (WELA) - Yoram Yudhatama (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2022)
Background: Heart disease in pregnancy is one of the leading causes of morbidity and mortality in pregnancy and childbirth. The intrapartum and postpartum periods are critical periods in which most of the deaths occur in this period. Manifestations appear in the form of heart failure which increases maternal and fetal morbidity and mortality.Case Illustration: We will report a case report of a 23-year-old woman with a diagnosis of G2P0A1 H 40 weeks, a single live intrauterine fetus with congestive heart failure due to rheumatic heart disease with mitral stenosis.Conclusion: The patient successfully underwent spontaneous labor under anesthesia facilitated by the walking epidural analgesia (WELA) technique with levobupivacaine and fentanyl agents which were administered continuously using a syringe pump during the labor process.